MENINGKATKAN PRESTASI BELAJAR IPA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - sumenari, Ketut (Journal of Education Action Reseach, 2018)
Research conducted in class VIII-B in SMP Negeri 1 Sukasada in the second semester of the academic year 2017/2018 aims to improve the learning process as well as to improve student achievement. The subjects of this study were taken from students who studied in Class VIII-B which amounted to 32 students, 20 men and 12 women. The object of this research is the effort to improve science achievement. Data collection techniques were conducted through tests (objective tests) and analyzed using descriptive analysis. Initial data only reached the average grade of 74.84 further in the first cycle increased by 2.97 to 77.81 and in cycle II also rose as much as 6.56 to become an average of 84.38. In learning completeness also increased from 64,86% initially increase as many as 16,22 in cycle I to become 81,08% and in cycle II also increase as many as 10,81 so become 91,89%. The data in cycle II shows that the expected success has been achieved even exceeds the indicator of the success of the proposed research. Thus the authors concluded that the model of Problem Based Learning applied in the process of learning science in class VIII-B SMP Negeri 1 Sukasada odd semester of the academic year 2017/2018 able to improve learning achievement